(untitled) (Al-Mansour Journal, 2022)
Abstract: The importance of this research come from the aspect of international criminal court and their judicial specialization in justice the state’s affiliates about the limited crimes enter within their specialist . at the same time these crimes mentioned on the judicial rules or even punishment laws of their countries . So , the legal paradox will raise as a result of different between their specialization in application of positive rules with respect to the national courts, so that the manner require to search about this paradox . Where the recent research explore to know the truth of international criminal court and the role played by charged the actually affection for the human rights. and the ways from to solve this dispute occur as a various specialization , from other side the privacy of specify the appropriate court to achieve like these claims from the view of penal claims . The various cases in which belong to this type of research , this study depend on the logical and analytical method , to demonstrate some opinions related to the research topics and analysis . The Research restrict to divide it in to three themes : First one deal with judicial specialization for international criminal court Second : processes of claims in front of criminal court Third : specialization dispute from the view of penal claims . The research ended by conclusion shown the most results and recommendations